PENENTUAN METODE ANALISIS DATA CURAH HUJAN YANG HILANG DI SUB - DAS MELAWI - Ferdyansyah, Syarif Muhammad; Stefanus Barlian Soeryamassoeka; Eko Yulianto (UKI Press, 2024)
ABSTRACT In hydrological analysis, rainfall intensity data has a very important role and accurate rainfall intensity data input is needed both temporally and spatially. The constraints experienced in Melawi Sub-watershed is the lack of availability of rainfall observation stations which resulted in the lack of rainfall data and loss of data at certain stations and periods. The results of this study are an analysis of 8 (eight) rainfall observation stations in Melawi Sub-watershed, namely STG-01 Sintang, STG-16 Kota Baru, STG-03 Nanga Pinoh, Stasiun BMKG Nanga Pinoh, Stasiun BMKG Susilo, STG-12 Batu Buil, STG-02 Nanga Sepauk, STG-08 Serawai. An alternative that can be used is to fill in missing rainfall data using 5 (five) methods, namely: normal ratio method, reciprocal method, random number method, and Markov chain stochastic analysis method and another alternative is to test the filling method using the rainfall data correction equation from the validated Tropical Rainfall Measuring Mission (TRMM) satellite, namely: Y = 0.373X + 20.182 where Y is synthetic data and X is historical data. Furthermore, from each method, error testing is carried out to get the percentage error of the synthetic data results obtained. The results show that of the five methods above, the average error of the correction equation method Y = 0.373X + 20.182 is 31,96%, which is the smallest percentage value compared to the Markov chain stochastic analysis method 57,86%; Normal Ratio method 62,87%; Random Number method 74,40%; Reciprocal method 83,77%. Key words : Equation of Correction; Error Percentage; Filling Method; Rainfall